2022
DOI: 10.3389/fnhum.2022.920659
|View full text |Cite
|
Sign up to set email alerts
|

Infra-Low Frequency Neurofeedback: A Systematic Mixed Studies Review

Abstract: IntroductionNeurofeedback training is increasingly applied as a therapeutic tool in a variety of disorders, with growing scientific and clinical interest in the last two decades. Different Neurofeedback approaches have been developed over time, so it is now important to be able to distinguish between them and investigate the effectiveness and efficiency characteristics of each specific protocol. In this study we intend to examine the effects of Neurofeedback based on slow brain activity, the so-called Infra-Lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Here the use of the term endogenous neuromodulation to refer to the absence of overt reinforcers was introduced-likely for the first time. A systematic mixed studies review has just been published (Bazzana et al, 2022). It reports on 18 studies of ILF NF and the alternative of reward-based training on Infra-Slow Fluctuations.…”
Section: Resultsmentioning
confidence: 99%
“…Here the use of the term endogenous neuromodulation to refer to the absence of overt reinforcers was introduced-likely for the first time. A systematic mixed studies review has just been published (Bazzana et al, 2022). It reports on 18 studies of ILF NF and the alternative of reward-based training on Infra-Slow Fluctuations.…”
Section: Resultsmentioning
confidence: 99%
“…ILF oscillations seem to be related to some neurophysiological processes, such as cerebral vasomotor fluctuations, cortical excitability, and heart-rate variability [48]. The therapeutic effectiveness of ILF neurofeedback seems promising for various symptoms (for a recent review on this subject, see Bazzana 2022) [49]. In chronic pain conditions, two studies demonstrated encouraging findings.…”
Section: Ilf Neurofeedbackmentioning
confidence: 99%
“…The focus on infralow fluctuations for neurofeedback protocols is relatively new and has not been implemented as often as brain activity ranging from 8 to 25 Hz [49]. ILF fluctuations (<0.1 Hz) of blood oxygenation levels (BOLD signals) have been found in chronic-pain patients using fMRI [65].…”
Section: Ilfmentioning
confidence: 99%
See 2 more Smart Citations